Ponadnarodowe korporacje jako podmioty nieformalnego wpływu na przykładzie zaangażowania w działania skierowane do osób LGBT w Polsce - Bielska, Beata; Tamborska, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper explores the assertion about multi-faceted tools of impact used by large corporations that they aim to limit the subjectivity of consumers. It is based on the concept of ‘deep capture’ developed by Jon Hanson and David Yosifon. According to this concept consumers have only the idea of their own subjectivity. The authors’ basic assumption is that human behaviour is largely (but not completely) dependent on external situational factors rather than the individual dispositions of individuals. In this context we analyse the role of large corporations in shaping the image of LGBT people in Poland. Noteworthy seems to be the consideration to build and strengthen the belief that LGBT people are a group which suffers discrimination, to which anyone should make gestures of support throughout consumer decisions. An overview of the activities of business entities for LGBT groups in Poland lets us say that they cannot be called large scale actions. The actions of Polish companies can be recognised as not very intensive. Western transnational corporations have huge experience in actions for LGBT people, but this is not necessarily the case in Poland.